Early effect of percutaneous coronary intervention of non-left anterior descending artery on coronary flow velocity reserve of left anterior descending artery assessed by transthoracic Doppler echocardiography. - Masahiro Hada (Public Library of Science (PLoS), 2021)
Background Limited data are available regarding the influence of percutaneous coronary intervention (PCI) of non-totally occluded lesions (non-CTO) on the coronary flow of non-target vessels. We sought to investigate the short-term impact of the non-left anterior descending artery (non-LAD) PCI on the coronary flow physiology of LAD using transthoracic Doppler echocardiography (TDE). Methods and results We consecutively studied 50 patients who underwent successful PCI of non-LAD and non-CTO lesions and a coronary flow velocity assessment of LAD at rest and maximal hyperemia before and at 2 days after the procedure by TDE. Coronary flow velocity reserve (CFVR) was calculated as the ratio of hyperemic to resting diastolic peak velocity (hDPV/bDPV). We evaluated the changes in LAD coronary flow characteristics after PCI of non-LAD and explored the determinants of the change in LAD-CFVR. The median fractional flow reserve (FFR) of the culprit lesion and the LAD quantitative flow ratio (QFR) were 0.67 and 0.88, respectively. After non-LAD PCI, LAD-CFVR was decreased in 33 patients (66.0%). LAD-CFVR significantly decreased (pre-PCI: 2.41, post-PCI: 2.03, p = 0.001) due to a significant decrease in LAD-hDPV (P = 0.007). The prevalence of impaired LAD-CFVR (≤2.0) significantly increased (pre: 30%, post: 48%, P = 0.027). Multivariable linear regression analysis showed that pre-PCI LAD-CFVR was independent predictor of the change in LAD-CFVR after PCI. Conclusions LAD-CFVR significantly decreased after successful non-LAD PCI due to the postprocedural reduction of coronary flow assessed by LAD-hDPV.